The Concept of Human Nature in Islam and Its Implications for the Social Behavior of the Muslim Community - Muhammad Yusuf; Muhammad Eissawy Abu El Yazid; Ahmad Faizal Syahrul Azmi (PT Barkah Ilmi Fiddunya, 2025)
The concept of the essence of humanity in Islam emphasizes that humans are created by Allah SWT as noble beings with the primary purpose of worshipping Him and serving as stewards (khalifah) on earth. Humans are endowed with intellect, conscience, and an innate nature (fitrah) that distinguishes them from other creatures. The essence of humanity in Islam encompasses three main dimensions: spiritual (ruhaniyah), intellectual (aqliyah), and social (ijtimaiyah). As stewards, humans have the responsibility to cultivate the earth, maintain the balance of nature, and uphold justice. As servants of Allah, humans are required to constantly worship and draw closer to Him through all activities performed with sincere intentions. Understanding this essence of humanity has profound implications for the social behavior of Muslims, encouraging them to uphold justice, promote equality, and care for social welfare. Values such as mutual assistance, solidarity, and tolerance form the foundation for building harmonious social interactions. However, Muslims also face challenges in implementing this concept, such as individualism, social injustice, and moral degradation. To address these challenges, serious efforts are needed through religious education, the enforcement of Islamic values in society, and the development of collective awareness of social responsibility. By understanding and practicing the concept of the essence of humanity in Islam, Muslims can build a just, harmonious, and civilized society